Pengaruh Model Pembelajaran Problem Based Learning dengan Strategi Alat Peraga Puzzle Dadu terhadap Minat Belajar dan Hasil Belajar Matematika Siswa Kelas VIII Materi Peluang SMPN 1 Sumbergempol Tulungagung Tahun Ajaran 2017/2018 - Nurul Aisyanah; Zunaida Kurniasari (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
This study aims to determine whether or not the influence of learning model probelm based learning strategy dizzy puzzle tool against the interest of learning and learning outcomes mathematics. This research uses quantitative approach and experiment type. This research was conducted in SMPN 1 Sumbergempol Tulungagung class VIII academic year 2017/2018 opportunity material. The result of research using 5% significance level is found that (1) there is no influence of problem based learning model with dice puzzle tool strategy to the interest of learning mathematics, this using wald-wolfowitz test with SIG (1-tailed) number of maximum posible is 1 >0,05, (2) there is influence of learning problem based learning model with puzzle props strategy toward mathematics learning result, this using moses test with GIS number (1-tailed) is 0,008 <0,05, (3) there is influence of problem-based learning model with dice puzzle tool strategy toward learning interest and learning achievement of mathematics. It uses kolmogorov-smirnov test with GIS number (2-tailed) from Asymp.SIG (2-tailed) number is 0, 0000 <0,05.